2022
DOI: 10.1007/s00417-022-05676-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual improvement and regeneration of retinal layers in eyes with small, medium, and large idiopathic full-thickness macular holes treated with the inverted internal limiting membrane flap technique over a period of 12 months

Abstract: Purpose This study aims to compare the improvement of best-corrected visual acuity (BCVA) and the reduction in defect length of external limiting membrane (ELM) and ellipsoid zone (EZ) in small ($$<$$ < 250 μm), medium ($$\ge$$ ≥ 250 μm), and large ($$\ge$$ ≥ 400 μm) full-thickness macular holes (FTMH) treated with inverted internal limiting membrane (I-ILM) flap technique over a follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is possible that the early improvement in visual function noted by these authors arises from the superior initial closure rates, and at later time points after revision surgery in non-closed holes the effect diminishes. It has also been hypothesised that ILM flaps may mechanically obstruct the restoration of the ellipsoid zone and external limiting membrane, essential to good post-operative visual function in FTMH repair [ 29 32 ]. Future studies with larger cohorts and long follow-up of at least 12 months are required to evaluate whether the initial impact of increased primary closure is accompanied by any beneficial or detrimental effect on post-operative visual function.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the early improvement in visual function noted by these authors arises from the superior initial closure rates, and at later time points after revision surgery in non-closed holes the effect diminishes. It has also been hypothesised that ILM flaps may mechanically obstruct the restoration of the ellipsoid zone and external limiting membrane, essential to good post-operative visual function in FTMH repair [ 29 32 ]. Future studies with larger cohorts and long follow-up of at least 12 months are required to evaluate whether the initial impact of increased primary closure is accompanied by any beneficial or detrimental effect on post-operative visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors reported that the defects in the EZ and ELM were a major reason for unsatisfactory postoperative visual recovery 16,19,24,26 . Nevertheless, Ooka et al 17 reported that IS/OS and ELM defect changes are not related to the changes of BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, it may be a wise choice to adopt a single-layer inverted ILM flap technique for large (.400 mm), medium, and small MHs in clinical practice. 22,23 A single-layer inverted ILM flap highly avoids the formation of gliotic tissue in the fovea associated with inserting the ILM into the hole, which is believed to interfere with the fovea morphologic restoration and visual function recovery. 23 According to the MH closure morphology classification by Imai et al, 24 in this study, at the last follow-up, 12 eyes (83.3%; 12/18) showed a U-type closure; five eyes (cases 2, 3, 8, 17, and 18; 5/18) showed a V-type closure; and one eye demonstrated a W-type closure (case 6; 1/18).…”
Section: Discussionmentioning
confidence: 99%